Patterns of functional connectivity in an aging population: The Rotterdam Study - Zonneveld, Hazel I.; Pruim, Raimon HR; Bos, Daniel; Vrooman, Henri A.; Muetzel, Ryan L.; Hofman, Albert; Rombouts, Serge ARB; van der Lugt, Aad; Niessen, Wiro J.; Ikram, M. Arfan; Vernooij, Meike W. (NeuroImage (Orlando, Fla.), 2019)
Structural brain markers are studied extensively in the field of neurodegeneration, but are thought to occur rather late in the process. Functional measures such as functional connectivity are gaining interest as potentially more subtle markers of neurodegeneration. However, brain structure and function are also affected by ‘normal’ brain ageing. More information is needed on how functional connectivity relates to aging, particularly in the absence of overt neurodegenerative disease. We investigated the association of age with resting-state functional connectivity in 2878 non-demented persons between 50 and 95 years of age (54.1% women) from the population-based Rotterdam Study. We obtained nine well-known resting state networks using data-driven methodology. Within the anterior default mode network, ventral attention network, and sensorimotor network, functional connectivity was significantly lower with older age. In contrast, functional connectivity was higher with older age within the visual network. Between resting state networks, we found patterns of both increases and decreases in connectivity in approximate equal proportions. Our results reinforce the notion that the aging brain undergoes a reorganization process, and serves as a solid basis for exploring functional connectivity as a preclinical marker of neurodegenerative disease. •The aging brain undergoes a complex functional reorganization process.•Age is related to decreases in within-network functional connectivity and to widespread increases and decreases in (anti-)correlations between different networks.•This study forms a basis for exploring functional connectivity as a preclinical marker of neurodegenerative disease.